When prisoners dare to become scholars: prison education as resistance. Issue 1 (2nd January 2019) - Key, Adam; May, Matthew S.
ABSTRACT: As an introduction to this special issue on prison education, this article seeks to radically reframe how academic literature addresses and understands the carceral classroom. The primary lens through which prison education is evaluated is as a means of reducing recidivism. In this rhetorical autoethnography, we write back against that assertion, arguing that prison education is far more than a tool for crime reduction. Using a series of autoethnographic glimpses, we offer a view inside the classroom behind bars and demonstrate that prison education is a means of resistance. By choosing to attend classes, prisoners defy gendered norms of hegemonic masculinity in order to resist the societal norm that prisoner lives do not matter.